The Simulation Game AMANJARI (I Independent Keep My Self) Social Mitigation of Sexual Violence on Children in Five Elementary School Areas of Kediri - Puji Lestari; Siti Fatimatuz Zahro; Wahyu Sugiharti; Novan Sandika; Mumun Nurmilawati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The phenomenon of sexual violence on children especially elemantary school children in the Region Kediri very worrying. This research aims to improve understanding of students about how to keep away from sexual violence. The research uses a method of pre experiment. Design the research uses pretest-postest design. Game simulation AMANJARI is applied to 2 grade elementary school was carried out in five primary schools in the Region of Kediri includes Kedak1 elemantary school, Karangtalun 1 elemantary school, Tarokan 1 elemantary school, Mojoroto 3 elemantary school and Kandangan 1 elemantary school with a total of 181 students. Research instruments used in the game decks AMANJARI designed resembling a monopoly, Pocketbooks AMANJARI as a guide the game, the evaluation for the pretest and postest. The result of the application of the simulation game AMANJARI namely the increase in the students understanding about how to guard against sexual acts of violence is as follows Kedak 1 elemantary school (17, 86%), Karangtalun 1 elemantary school (12,53%), Tarokan 1 elemantary school (17,24%),  Mojoroto 3 elemantary school (2,38%) and Kandangan 1 elemantary school (1,58%). The game AMANJARI shown to enhance the knowledge of students about how to keep yourself and can prevent the occurrence of sexual violence so as to reduce the impact of sexual violence on children in the Region of Kediri.Keywords:        children, sexual violence, simulation games AMANJARI